Comparative Transcriptome Analysis of the Phototrophic Dinoflagellate Biecheleriopsis adriatica Grown Under Optimal Temperature and Cold and Heat Stress - Kang, Hee Chang; Jeong, Hae Jin; Park, Sang Ah; Ok, Jin Hee; You, Ji Hyun; Eom, Se Hee; Park, Eun Chong; Jang, Se Hyeon; Lee, Sung Yeon (Frontiers in Marine Science, 2021)
Dinoflagellates are a major component of marine ecosystems, and very cold and hot water may affect their survival. Global warming has amplified the magnitude of water temperature fluctuations. To investigate the molecular responses of dinoflagellates to very cold and hot water, we compared the differentially expressed genes of the phototrophic dinoflagellate Biecheleriopsis adriatica grown under optimal temperature and cold and heat stress. The number of genes upregulated or downregulated between optimal temperature and cold stress was twice than that between optimal temperature and heat stress. Moreover, the number of upregulated genes was greater than that of the downregulated genes under cold stress, whereas the number of upregulated genes was less than that of the downregulated genes under heat stress. Furthermore, among the differentially expressed genes, the number of genes upregulated under cold stress and with unchanged expression under heat stress was the highest, while the number of the genes downregulated under cold stress, but not under heat stress, was the second-highest. Facilitated trehalose transporter Tret1 and DnaJ-like subfamily B member 6-A were upregulated and downregulated, respectively, under cold stress; however, their expression remained unchanged under heat stress. In contrast, Apolipoprotein d lipocalin and Troponin C in skeletal muscle were upregulated and downregulated, respectively, under both cold and heat stress. This study provides insight into the genetic responses of dinoflagellates to climate change-driven large water temperature fluctuations.